2016
DOI: 10.1007/s11524-016-0089-y
|View full text |Cite
|
Sign up to set email alerts
|

Angry, Scared, and Unsure: Mental Health Consequences of Contaminated Water in Flint, Michigan

Abstract: Natural and manmade crises impact community-level behavioral health, including mental health and substance use. This article shares findings from a larger project about community behavioral health, relevant to the ongoing water crisis in Flint, Michigan, using data from a larger study, involving monthly surveys of a panel of key informants from Genesee County. The data come from open-response questions and are analyzed as qualitative data using grounded theory techniques. Although respondents were not asked ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
85
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 29 publications
5
85
0
Order By: Relevance
“…These and other factors create a disaster ecology in which various forces of harm impact individuals, communities, and societies (3). For example, cultural and contextual factors were critical to community partnership and effective response in: 1) Haiti earthquake in 2010 required knowledge about and incorporation of voodoo as a religious ritual integral to how citizens conceptualized and responded to healthcare interventions (4), 2) West Africa Ebola virus outbreak in 2000 necessitated awareness and collaboration with local communities to incorporate the importance of faith-based burial rituals (5), 3) Flint, Michigan lead water crisis in 2015 was experienced by community members as further evidence of systemic racial inequities that further eroded public trust (6). Each of these events, as with all disasters, necessitated an understanding of sociocultural and contextual factors within the communities to optimize response and recovery efforts.…”
Section: Disasters and Public Healthmentioning
confidence: 99%
“…These and other factors create a disaster ecology in which various forces of harm impact individuals, communities, and societies (3). For example, cultural and contextual factors were critical to community partnership and effective response in: 1) Haiti earthquake in 2010 required knowledge about and incorporation of voodoo as a religious ritual integral to how citizens conceptualized and responded to healthcare interventions (4), 2) West Africa Ebola virus outbreak in 2000 necessitated awareness and collaboration with local communities to incorporate the importance of faith-based burial rituals (5), 3) Flint, Michigan lead water crisis in 2015 was experienced by community members as further evidence of systemic racial inequities that further eroded public trust (6). Each of these events, as with all disasters, necessitated an understanding of sociocultural and contextual factors within the communities to optimize response and recovery efforts.…”
Section: Disasters and Public Healthmentioning
confidence: 99%
“…Thus, variations in pH, salinity, and the properties of the redox potential can cause the mobilization and resuspension of chemical particles accumulated in the sediments, magnifying even its toxic effect, such as the case of heavy metals. Heavy metals are largely derived from anthropogenic sources, such as domestic, agricultural, and industrial waste, and constitute a danger to aquatic biota and human beings, as well representing an environmental deterioration factor [7].…”
Section: Introductionmentioning
confidence: 99%
“…this devaluation is based on both their blackness and their surplus status, with the two being mutually constituted. (p. 1) Additional research has found that exposure to the Flint water crisis has been linked to both physical (Sadler et al, 922942H EBXXX10.1177 1 University of California Merced, Merced, CA, USA 2017) and mental (Cuthbertson et al, 2016) health problems for poor and people of color and can be explained through multiple mechanisms, such as disinvested, racially segregated neighborhoods (Michigan Civil Rights Commission 2017).…”
mentioning
confidence: 99%